2017
DOI: 10.4111/icu.2017.58.5.378
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of urinary dipstick pH: Are multiple dipstick pH readings reliably comparable to commercial 24-hour urinary pH?

Abstract: PurposeAccurate measurement of pH is necessary to guide medical management of nephrolithiasis. Urinary dipsticks offer a convenient method to measure pH, but prior studies have only assessed the accuracy of a single, spot dipstick. Given the known diurnal variation in pH, a single dipstick pH is unlikely to reflect the average daily urinary pH. Our goal was to determine whether multiple dipstick pH readings would be reliably comparable to pH from a 24-hour urine analysis.Materials and MethodsKidney stone patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…More importantly, the Bland-Altman plot indicated that the dipstick measured urine pH 0.28 units higher than the reference method, which was within the limits of acceptability of ≤0.50 pH units. The small positive bias was similar to that reported in dog urine (+0.22; Johnson et al, 2007) but different from findings in other species, where a bias of −0.22 was identified in human urine (Abbott et al, 2017), −0.02 in sheep urine (Athanasiou et al, 2018), and −0.12 in cat urine (Raskin et al, 2002). The difference in analytical performance of the dipstick may be due to species differences in urine color.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…More importantly, the Bland-Altman plot indicated that the dipstick measured urine pH 0.28 units higher than the reference method, which was within the limits of acceptability of ≤0.50 pH units. The small positive bias was similar to that reported in dog urine (+0.22; Johnson et al, 2007) but different from findings in other species, where a bias of −0.22 was identified in human urine (Abbott et al, 2017), −0.02 in sheep urine (Athanasiou et al, 2018), and −0.12 in cat urine (Raskin et al, 2002). The difference in analytical performance of the dipstick may be due to species differences in urine color.…”
Section: Discussionsupporting
confidence: 53%
“…The acceptable limits for U pH-MS and U pH-HP were considered to be ≤0.5 pH units compared with the reference method (U pH ). Acceptable limits were based on the results of other studies (Heuter et al, 1998;Kwong et al, 2013;Abbott et al, 2017), the resolution of U pH-MS measurement, and personal observations that variations in U pH of this magnitude commonly occur over a 24-h period in cattle fed a TMR.…”
Section: Discussionmentioning
confidence: 99%
“…Various dipsticks may differ in their diagnostic performance regarding leukocyte and erythrocyte detection ( 5 ). There is also evidence that urine dipstick pH analysis shows insufficient accuracy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary pH varies throughout the day and the decision to acidify or alkalize urine is generally not based on an isolated urine sample. [15][16][17] It is important that caregivers and patients possess accurate pH measuring devices. Since pH is a logarithmic scale, an increase in one pH unit means a tenfold decrease in acidity or hydrogen-ion concentration.…”
Section: Resultsmentioning
confidence: 99%